Periodontitis and systemic inflammation as independent and interacting risk factors for mortality: evidence from a prospective cohort study - Christiane Pink; Birte Holtfreter; Henry Völzke; Matthias Nauck; Marcus Dörr; Thomas Kocher (BMC Medicine)
Abstract Background Recent studies have highlighted the role of low-grade systemic inflammation in linking periodontitis to cardiovascular disease (CVD) outcomes, but many aspects remain unclear. This study examines the independent and reciprocal associations of periodontitis and low-grade systemic inflammation with all-cause and CVD mortality in a large-scale cohort. Methods A total of 3047 participants from the prospective, population-based Study of Health in Pomerania (SHIP-START) were followed for a period of 13.0 ± 2.4 years. For the association between various inflammation/periodontitis measures and mortality, hazard ratios (HRs) were obtained from covariate-adjusted Cox proportional hazards models. Interactions were analysed in joint models: on the multiplicative scale, HRs were reported and on the additive scale, relative excess risks due to interaction (RERI) were calculated. Subject and variable-specific interval records were used to account for time-varying exposures and covariates. Results During the observation period, 380 (12.5%) individuals died from CVD (n = 125) or other causes (n = 255). All markers of periodontitis and inflammation showed apparent associations with all-cause mortality (HRs per SD-increase: mean PPD: 1.068 (95% confidence interval (CI): 0.988–1.155), mean CAL: 1.205 (95% CI: 1.097–1.323), missing teeth: 1.180 (95% CI: 1.065–1.307), periodontitis score: 1.394 (95% CI: 1.202–1.616), leukocytes: 1.264 (95% CI: 1.163–1.374), fibrinogen: 1.120 (95% CI: 1.030–1.218), CRP: 1.231 (95% CI: 1.109–1.366), inflammation score: 1.358 (95% CI: 1.210–1.523)). For CVD mortality, all PPD related variables showed significant associations. Interaction modelling revealed some variation with respect to mortality type and exposure combinations. On the additive scale, RERIs for periodontitis score and inflammation score implied 18.9% and 27.8% excess mortality risk for all-cause and CVD mortality, respectively. On the multiplicative scale, the HRs for interaction were marginal. Conclusions Both periodontitis and inflammation were significantly associated with all-cause mortality and CVD mortality. On the additive scale, a substantial excess risk was observed due to the interaction of periodontitis and inflammation, suggesting that the greatest treatment benefit may be achieved in patients with both periodontitis and high systemic inflammation. As periodontal therapy has been reported to also reduce systemic inflammation, the possibility of a reduction in CVD mortality risk by anti-inflammatory treatments, including periodontal interventions, seems worthy of further investigation.